What are the key roles of education? - Rogošić, Silvia (Array, 2020)
The position of education in society depends to a certain degree on the public opinion about what education should provide to an individual and the social community.1 In fact, in addition to the humanistic aim of education implying a versatile (complete, harmonious) or self-actualising development of an individual,2 the scientists often emphasise the social, political, and economic purpose of education. Thus, education, for example, has a very important role in ensuring economic and social progress and improving the distribution of income.3 In addition, the educational system is also viewed as a social agent that transfers the norms and values important for the preservation of a stable political system.4 Although there is abundant theoretical literature exploring these approaches and analysing them in detail, there is a lack of empirical research on how individuals perceive the importance of certain educational roles and what factors determine their points of view. It is particularly important to examine the opinion of preschool teachers and teachers on educational roles because they have an impact on the shaping of educational policies and pedagogical practices. Therefore, quantitative research was conducted on a sample of preschool teachers in the City of Zagreb (N = 481). The aim of this research is to examine which educational goals are prioritised by preschool teachers in terms of the main purpose of education and to provide empirical insights into the correlation of certain characteristics of the respondents (socio-demographic characteristics and religious affiliation) and their perception of the purpose of education. Thefindings show that the majority of respondents agree that education should primarily serve the development of a free and independent individual.